Successful management of left side pre-cervical uterine torsion in a Gir cow - Kumar, Brijesh; Rashid, Muzamil; Vandana; Kumar, Naveen; Singh, Mohar; Lokavya, Athidi; Chandra, Pradeep; Kumar, Abhishek (The Indian Journal of Animal Reproduction, 2022)
An 8 years old Gir cow in third parity with a history of completed gestation period and unsuccessful attempts to correct the torsion was presented. Per-rectal examination revealed left-sided, pre-cervical uterine torsion of more than 180o. After the arrival of the case at the Referral Veterinary Polyclinic (RVP), IVRI, Izatnagar, the case was stabilized through fluid therapy and other supportive treatment, and an attempt was made to correct the torsion through Sharma’s Modified Schaffer’s method but, it remained unsuccessful. So, cesarean section was performed and a dead emphysematous fetus was extracted and after suturing of uterus, detorsion was done within abdominal cavity.